The Eurasian Integration as an Example of Modern Integration Process in the Conditions of Instability - Andrey Andreevich Kovalev (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
In the article, the concept of the Eurasian integration as a modern priority in the field of development and modernization is considered. In this work integration is investigated not so much as coordination of economic procedures but as formation not quantitative, but high-quality changes considering that huge number of structural geopolitical and geoeconomic changes that has created need of forming of new modern mechanisms and tools of system of the international relations with the purpose of formation of the updated architecture of relationship of the modern states, nations, cultures and civilizations. In addition, dynamics of these changes and forms of their variety which have increased in a geometrical progression after the 90th years of the XX century that has raised a set of questions concerning formation of modern international, national and state administrative and social technologies is considered. Especially sharply, the perspective of the matter concerns integration of the former Soviet Union, in view of a difference of views of the western states and countries of the region of the CIS and the East on understanding of essence and mechanisms of integration, taking into account a universal tendency to regionalization process as to a globalization